“Efecto de la incorporación de microorganismos eficientes en la elaboración del compost, distrito de la banda de Shilcayo – San Martín – Perú - Velasco Flores, Héctor (2014)
The present work of titled investigation: "Effect of the lncorporation of Efficient Microorganisms in the process of decomposition of the Organic Matter", has like objectives: 1) To determine the time of decomposition of the organic matter, 2) To determine the effect that will have the efficient microorganisms in the quality of compost obtained and 3) To determine the relation cost/benefits of the treatments. The present work was realised in the E. E. "Juan Bernito - ICT", for which a design of blocks at random (OSCA) with 5 treatments and 3 repetitions was used completely. The treatments in study were the following: T1 (100 kg of Vacaza + 100 kg of Strubble + 20 ce of efficient Microorganisms), T2 (100 kg of Gallinaza+ 100 kg of Strubble + 20 ce of efficient Microorganisms), T3 (100 kg of Vacaza + 100 kg of Strubble), T4 (100 kg of Gallinaza + 100 kg of Strubble), T5 (200 kg of Strubble). From which the following variables were evaluated: Chemical and Microbiological temperatura, Humidity, Characteristics, the obtained results indicate the following thing: The treatments that obtained the best chemical characteristics as as much microbiological have been the T2 (100 kg of Gallinaza+ 100 kg of Strubble + 20 ce of efficient Microorganisms) and the T4 (100 kg of Gallinaza + 100 kg of Strubble), which showed the following results: pH (6,96; 7, 17) , Nitrogen (1,55; 1,54), Phosphorus (2,43; 2,43), Potassium (1,74; 1,78) Calcium (6,93; 7,04), Magnesium (0,97; 0,94), Manganese (350,07; 343,73), Sulphur (5,15; 5,70), Boron (105,07; 129,20), lron (7068,05; 6858,82). Zinc (448,13; 437,61), Receives (57,91; 46,64), fungí (5, 19E+05 UFC/gr Suelo; 4,99E+05 UFC/gr Suelo), with the best sort: "Trichodermasp; bacteria (3.27 E+06 UFC/gr. Ground; 3,01 E+06 UFC/100 gr. Ground); and the smaller populations of Nematodes (O IND /100 gr. Ground). Referring to the relation Cost/benefits, the treatments that they obtained major gain were the T2 treatments (100 kg of Gallinaza+ 100 kg of Strubble + 20 ce of efficient Microorganisms) and the T4 (100 kg of Gallinaza+ 100 kg of Strubble) T2 (14.18%), T4 (14.43%), which obtained a gain of 0.86 new suns by each inverted sun. Key words: Abonos orgánicos, rastrojos, Microorganismos eficientes, Trichodermasp.